2011
DOI: 10.1073/pnas.1107892109
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Piwi functions downstream of piRNA production mediating a chromatin-based transposon silencing mechanism in female germ line

Abstract: Transposon control is a critical process during reproduction. The PIWI family proteins can play a key role, using a piRNA-mediated slicing mechanism to suppress transposon activity posttranscriptionally. In Drosophila melanogaster , Piwi is predominantly localized in the nucleus and has been implicated in heterochromatin formation. Here, we use female germ-line–specific depletion to study Piwi function. This depletion of Piwi leads to infertility and to axis specification defects in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
232
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(251 citation statements)
references
References 50 publications
14
232
0
1
Order By: Relevance
“…Other TEs with piRNA signals include HeT-A, I element, and copia (20). All three transposon families are silenced by HP1a and H3K9me2/3 assembly over their promoter elements in the female germ line by a mechanism dependent on RNAi components (22,37). piRNA biogenesis is most active at this stage, and it has been argued that its effects may be limited to germ cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other TEs with piRNA signals include HeT-A, I element, and copia (20). All three transposon families are silenced by HP1a and H3K9me2/3 assembly over their promoter elements in the female germ line by a mechanism dependent on RNAi components (22,37). piRNA biogenesis is most active at this stage, and it has been argued that its effects may be limited to germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…A third component, Piwi, is a nuclear protein that binds mostly antisense piRNAs, a subset of which are generated by ping-pong cycle-dependent piRNA biogenesis (17,20). Piwi interacts with HP1a and has been implicated in a transcriptional silencing role in the germ line (21)(22)(23). These piRNA components are loaded into the oocyte (17,24); their mode of TE repression in the early embryo has been relatively unexplored but could include a role in establishing heterochromatin domains.…”
Section: -Sensitive Silencing Is Observed In a Subset Of Euchromaticmentioning
confidence: 99%
“…Subsequently, the RNA products of this reaction may be loaded into the complementary Piwi-clade protein Ago3 for ping-pong amplification [107] (Box 1). Piwi also appears to initiate transcriptional gene silencing (TGS) by shuttling to the nucleus, recognizing transposon transcripts, and recruiting DNA [109,110] and/or chromatin modifiers, [111,112] which repress transcription of transposon loci (Box 2). This link between RNAi and heterochromatin formation is highly reminiscent of RNA induced transcriptional silencing (RITS) in budding yeast.…”
Section: Piwismentioning
confidence: 99%
“…Most piRNA sequences in the Drosophila genome map to heterochromatic regions (Saito et al 2006), and several lines of investigation have demonstrated that Piwi and HP1a can physically interact (Brower-Toland et al 2007;Mendez et al 2011). Moreover, transcriptional silencing of retrotransposons by the Piwi-piRNA system involves recruitment of HP1a to transposable elements (Wang and Elgin 2011;Sentmanat and Elgin 2012;Huang et al 2013). Piwi also participates in activities that are not directly related to transposon silencing.…”
mentioning
confidence: 99%